GAMBARAN HISTOPATOLOGI PARU TIKUS WISTAR SETELAH DIBERI PAPARAN ASAP ROKOK - Novera Herdiani; Endah Budi Permana Putri (Jurnal Ilmu Kesehatan dan Kesehatan, 2018)
Abstract: Cigarette smoke is the main cause of lung obstruction. One of the obstructions in real that iscaused by cigarette smoke is oxidative stress. Oxidative stress trigger inflammation response occur andlung obstruction. Cigarette smoke able to cause lung histopathology changes like lungs obstruction onalveolus wall. Red dragon fruit extract tackle free radical then able to against the oxidative stress. Theobjective of this study to examines the image of rat lung histopathology under exposed cigarette smoke.Twenty four Wistar rats divided four groups: negative control, positive control, red dragon fruit extracttreatment of 7,2 g/200 g WB, and red dragon fruit extract10,8 g/200 g WB. Negative control only givenstandard feed. Positive control given standar feed and exposed 21 cigarette per day. Treatment groupgiven feed during 21 days. In the 22nd day rats be sacrificed, the lung taken out for observation andimage of rat lung histopathology changes by making lung organ histopathology preparationhematoxicillin Eosion (HE) staining and observed under magnification light microscope 400x. The endresult of the study indicate the finding of changes in lung histopathology such as obstruction level overthe lung tissue higher, alveolar macrophage covered alveoli after being exposed cigarette smoke. Groupwhich does not exposed cigarette smoke, lung alveolus macrophage in normal condition, there are noobstruction or alveolus macrophage occurred, its alveolar macrophage does no covering alveoli.Treatment group administered fruit dragon extract dose 10,8 g/200 g WB and dose 7,2 g/200 g WB seemalmost the same with negative control treatment. Conclusion of the research is cigarette smoke exposecan influence the number of alveolar macrophage on wistar rats. Suggestion very required furtherresearch on oxdative stress parameter.